Physical Activity – Friend or Foe of Acne? A Literature Review - Dziuba, Natalia; Mioduszewska, Joanna; Sim, Aleksandra; Rot, Paweł; Poniewozik, Piotr; Pernal, Maja; Roguska, Zofia; Zuzak, Andrzej Pawel; Poniewozik, Paweł; Grabowski, Krzysztof (Quality in Sport, 2026)
Background: Acne is a multifactorial inflammatory skin condition influenced not only by local factors such as sebum production and follicular blockage, but also by systemic processes including hormonal regulation, metabolism, and lifestyle behaviors. Aim: This literature review aims to synthesize current evidence and evaluate the impact of physical activity on acne development and severity, considering both its potential beneficial and exacerbating effects. Methodology: A literature search was conducted to identify relevant studies published between 2006 and 2026 using electronic databases, including PubMed, Google Scholar, and ResearchGate. Results: Physical activity may exert both beneficial effects - through improved circulation, anti-inflammatory responses, and hormonal balance - and adverse effects, such as increased sweating, friction, and occlusion, making its overall role in acne development complex and potentially both protective and aggravating. Conclusions: Physical activity is commonly perceived to exacerbate acne, but this review indicates that observed associations are largely driven by environmental, mechanical, and metabolic factors rather than direct physiological effects. These findings emphasize the importance of separating myth-based beliefs from evidence-based mechanisms, while highlighting the need for further research across diverse populations and exercise contexts.